ANALISIS PERKEMBANGAN E-WALLET DAN PERAN TEKNOLOGI BLOCKCHAIN DALAM SISTEM PEMBAYARAN DIGITAL DI INDONESIA - Merisa Natalia; Natasya Priscilla; Dorie P. Kesuma (Jurnal Riset Teknik Komputer, 2026)
This study analyzes the development of e-wallet and the role of blockchain technology in digital payment systems in Indonesia. The rapid advancement of digital technology and the increasing internet penetration have encouraged the transformation of financial transactions from cash-based systems to digital payments. E-wallet services have become increasingly popular due to their practicality, speed, and efficiency in supporting daily transactions. However, the growth of digital payment systems also raises various security challenges, such as data breaches, fraud, and transaction manipulation. Therefore, blockchain technology emerges as an innovative solution that offers decentralization, transparency, and high security through immutable transaction records and distributed ledger systems. This research uses a descriptive qualitative method with a literature study approach by analyzing journals, reports, and related scientific references regarding e-wallet, fintech, and blockchain implementation in Indonesia. The results of the study indicate that blockchain implementation has a positive impact on improving transaction security, transparency, efficiency, and trust in digital payment systems. Blockchain technology can reduce fraud risks, accelerate transaction processes, minimize operational costs, and support the development of a more secure and efficient digital financial ecosystem. However, several challenges remain, including regulatory readiness, infrastructure limitations, implementation costs, and low levels of digital literacy. Therefore, collaboration between the government, fintech companies, and society is necessary to optimize blockchain implementation in Indonesia’s digital payment systems.